Digital constant‐envelope modulation scheme for radar using multicarrier OFDM signals. Issue 7 (1st September 2017) - Qian, Rong; Jiang, Defu; Fu, Wei
Abstract : Multicarrier signals using orthogonal frequency division multiplexing (OFDM) bring many advantages to radar such as low probability of intercept, improved target detection performance, optimisation of both radar transmitter and receiver etc. A major drawback of multicarrier OFDM signals is their high peak‐to‐mean envelope power ratio, which reduces the working efficiency of the used power amplifiers. To solve this problem, a digital constant‐envelope modulation scheme is proposed for radar using multicarrier OFDM signals. The scheme can transmit multicarrier OFDM signals through power amplifiers being operated near saturation levels (and thus maximising power efficiency) with little spectral distortion, even in the presence of channel mismatch. Given the speed limitations of field programmable gate arrays (FPGAs), the proposed scheme is implemented in an FPGA at intermediate frequency level using a polyphase processing structure.